VARIATIONS IN LEARNING INTEREST AMONG ELEMENTARY SCHOOL STUDENTS WHO PLAY ONLINE GAMES: A QUALITATIVE CASE STUDY - Isti Windi Astuti; Ana Andriani; Y. Suyitno; Wakhudin (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The learning interests of students who enjoy playing online games are an important aspect in improving the effectiveness of learning in elementary schools, especially in phase C (grades V and VI), who are experiencing cognitive and social development. This study aims to analyze the learning interests of phase C students who use online games. The qualitative research approach uses a case study design with subjects of phase C elementary school students, teachers, and parents in the Maos Cilacap cluster. Data collection was conducted through observation, interviews, and documentation studies. Data were analyzed using an interactive model that includes data condensation, data presentation, and drawing conclusions. Data validity was guaranteed through triangulation of sources and techniques. The results of the study show variations in the learning interests of students who use online games based on seven indicators: desire to learn, enjoyment, attention, interest, enthusiasm for learning, task completion, and adherence to rules. Some students have high interest, characterized by the ability to manage study and play time, consistent focus, interest in the material, active participation, diligent completion of tasks, and compliance with rules. The group with moderate interest shows sufficient motivation and attention; participation and task completion require direction, and compliance with rules varies. Some students exhibited low interest, as evidenced by inconsistent motivation, easy distraction from games, impaired focus, minimal participation, and low compliance. These findings underscore the importance of teachers and parents in guiding and creating a supportive learning environment, enabling online gaming activities to promote enjoyable, effective, and meaningful learning for students' cognitive, social, and emotional development.